2009
DOI: 10.1007/978-1-4419-1306-7_3
|View full text |Cite
|
Sign up to set email alerts
|

MetaBoosting: Enhancing Integer Programming Techniques by Metaheuristics

Abstract: International audienceThis chapter reviews approaches where metaheuristics are used to boost the performance of exact integer linear programming (IP) techniques. Most exact optimization methods for solving hard combinatorial problems rely at some point on tree search. Applying more effective metaheuristics for obtaining better heuristic solutions and thus tighter bounds in order to prune the search tree in stronger ways is the most obvious possibility. Besides this, we consider several approaches where metaheu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Nevertheless, this approach has a limited scope since it does not work effectively for generalised cases. Recent activities in the operation research community suggested the possibility of boosting performance for the ILP model by integrating with an efficient heuristic for tightening search space [17]. Enhancing ILP models with valuable information from the problem-specific heuristic is a promising technique for speeding up the running time performance and this opens up opportunities to leverage exact approaches for solving the RSA problem.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this approach has a limited scope since it does not work effectively for generalised cases. Recent activities in the operation research community suggested the possibility of boosting performance for the ILP model by integrating with an efficient heuristic for tightening search space [17]. Enhancing ILP models with valuable information from the problem-specific heuristic is a promising technique for speeding up the running time performance and this opens up opportunities to leverage exact approaches for solving the RSA problem.…”
Section: Introductionmentioning
confidence: 99%
“…4. Metaheuristics can be integrated with exact methods to improve the performance of the exact methods (Friden et al 1989;Glover 1990;Puchinger et al 2009). 5.…”
Section: Metaheuristics and Exact Methodsmentioning
confidence: 99%
“…While a complete review of such methods is beyond the scope of this paper, a few examples show the variety of approaches tried in this category. [38] developed a method they called MetaBoosting to use metaheuristics to improve column generation or cut separation in an integer programming framework. Using Ant Colony Optimisation with Constraint Propagation has been shown to be effective in [48].…”
Section: Introductionmentioning
confidence: 99%